Molecular determinant for specificity: differential interaction of alpha-amylases with their proteinaceous inhibitors - Rane, Ashwini S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: alpha-Amylase inhibitors (alpha-AIs) belong to the discrete classes, and exhibited differential specificities against alpha-amylases from various sources. Several alpha-amylases and their complexes with inhibitors at the molecular level have been studied in detail. Interestingly, some alpha-AIs depict specific and selective interactions amid different insect alpha-amylases. Scope of review: There are studies to understand evolutionary variability and functional differentiation of insect alpha-amylases and their cognate inhibitors. We have examined sequence, structural, and interaction diversity between various alpha-amylases and alpha-AIs. Based on these analyses, we are providing a potential basis for the functional differentiation among certain insect a-amylases concerning mammalian counterparts and their interactions with different proteinaceous alpha-AIs. Major conclusions: Insect alpha-amylases have conserved domain architecture with differences in length, number of disulfide bonds, and secondary structure. Furthermore, few of them exhibit variable characteristics like chloride dependent activity, the presence of N-terminal glutamine residue to protect against proteolytic degradation, and loop variations near the enzyme active site. Conformation of alpha-AI protein could be an essential factor for their specificity and binding affinities towards target alpha-amylase(s). Furthermore, variation into the enzyme binding pocket residues might contribute to differential interactions with inhibitors. General significance: Molecular insights in the interactions between insect alpha-amylases and plant alpha-AI will provide the details of mechanisms assisting the inhibitor specificity. Furthermore, this information will help to design potent and effective alpha-AIs against specific alpha-amylase.
Keywords: Active site; alpha-amylase; alpha-amylase inhibitor; Insect; molecular interactions

Molecular investigation of coleopteran specific alpha-amylase inhibitors from amaranthaceae members - Rane, Ashwini S.; Venkatesh, Varun; Joshi, Rakesh S.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2020)
alpha-Amylase inhibitors (alpha-AIs) target alpha-amylases and interfere with the carbohydrate digestion of insects. Among different classes of alpha-AIs, a knottin-type inhibitor from Amaranthus hypochondriacus (AhAI) was found to be specific against coleopteran storage pests. In this report, we have characterized three previously unidentified knottin-type alpha-AIs from various Amaranthaceae plants namely, Amaranthus hypochondriacus (AhAI2), Alternanthera sessilis (AsAI) and Chenopodium quinoa (CqAI). They contain a signal peptide, pro-peptide, and mature peptide. The mature peptides of the new alpha-AIs shared 68 to 78% identity with AhAI and have highly variable pro-peptide regions. Along with the cystine-knot fold, they showed conservation of reactive site residues. All recombinant alpha-AIs were successfully expressed in their active form and native state using an oxidative cytoplasmic environment. Inhibition studies against various amylases revealed that these inhibitors showed selective inhibition of coleopteran recombinant insect alpha-amylases viz., Tribolium castaneum, and Callosobruchus chinensis. Tribolium castaneum alpha-amylase inhibition potency was highest for AhAI2 (Ki similar to 15 mu M) followed by AsAI (Ki similar to 43 mu M) and CqAI (Ki similar to 61 mu M). Interaction analysis of these inhibitors illustrated that the reactive site of inhibitors make several non-covalent interactions with the substrate-binding pocket of coleopteran alpha-amylases. The selectivity of these inhibitors against coleopteran a-amylases highlights their potential in storage grain pest control. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-amylase; alpha-amylase inhibitor; Amaranthaceae; Coleoptera; Knottin-type

Domain shuffling and site-saturation mutagenesis for the enhanced inhibitory potential of amaranthaceae α-amylase inhibitors - Rane, Ashwini S.; Nair, Vineetkumar S.; Joshi, Rakesh S.; Giri, Ashok P. (Protein Journal, 2023)
Amaranthaceae a-amylase inhibitors (AAIs) are knottin-type proteins with selective inhibitory potential against coleopteran a-amylases. Their small size and remarkable stability make them exciting molecules for protein engineering to achieve superior selectivity and efficacy. In this report, we have designed a set of AAI pro- and mature peptides chimeras. Based on in silico analysis, stable AAI chimeras having a stronger affinity with target amylases were selected for characterization. In vitro studies validated that chimera of the propeptide from Chenopodium quinoa a-AI and mature peptide from Beta vulgaris a-AI possess 3, 7.6, and 4.26 fold higher inhibition potential than parental counterparts. Importantly, recombinant AAI chimera retained specificity towards target coleopteran a-amylases. In addition, to improve the inhibitory potential of AAI, we performed in silico site-saturation mutagenesis. Computational analysis followed by experimental data showed that substituting Asparagine at the 6th position with Methionine had a remarkable increase in the specific inhibition potential of Amaranthus hypochondriacus a-AI. These results provide structural-functional insights into the vitality of AAI propeptide and a potential hotspot for mutagenesis to enhance the AAI activity. Our investigation will be a toolkit for AAI's optimization and functional differentiation for future biotechnological applications.
Keywords: & alpha; -Amylase; -Amylase inhibitors; Amaranthaceae; Coleoptera; Peptide; Pest control